GC-CR: A Decentralized Garbage Collector Component for Checkpointing in Clouds - Louati, Thouraya; Abbes, Heithem; Cérin, Christophe; Jemni, Mohamed (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2017)
Infrastructure-as-a-Service container-based virtualization technology is gaining significant interest in industry as an alternative platform for running distributed applications. With increasing scale of Cloud Computing architectures, faults are becoming a frequent occurrence. Checkpoint-Restart is a key method to survive to failures in this context. However, there is a need to reduce the amount of checkpointing data as the Cloud is based on the pay-as-you-go model. This paper addresses the issue of garbage collection in LXCloud-CR and contributes with a novel decentralized garbage collection component “GC-CR”. LXCloud-CR, a decentralized Checkpoint-Restart model, is able to take snapshots of Linux Container instances and it uses replication to increase snapshots availability. LXCloud-CR contains a versioning scheme for each replica. The disadvantage refers to snapshots availability issues with versioning as the number of useless files grows. GC-CR is a decentralized garbage collector (checkpoint deletion) component that attempts to identify and eliminate old snapshots versions from the system in order to free storage space. Large scale experiments on the Grid'5000 testbed demonstrate the benefits of our proposal. Obtained results validate our model and show significant reduction of storage space consumption.